Avaliação do potencial citotóxico, pró-apoptótico e anticlonogênico de lectinas isoladas de algas marinhas vermelhas das espécies Bryothamnion seafortii e Bryothamnion triquetrum - Silva, Renally Barbosa da (2022)
Cancer is a global public health issue and despite advances in treatment, they remain unspecific, costly and inefficient, mainly due to chemoresistance. The patterns of cellular glycosylation are altered during the differentiation of tumor cells and the process of metastasis, and therefore the cells stop responding to essential stimuli such as those from regulated cell death. Lectins that have been isolated from seaweed have unique molecular structures that can act to modulate cell death pathways and inhibit the pathways that are essential to tumor progression. In view of this, the aim of this study was to investigate the antitumor potential, in vitro, of isolated red algae lectins from Bryothamnion triquetrum (BTL) and Bryothamnion seaforthii (BSL), to combat tumor and non-tumor strains. The results showed that BTL and BSL were able to reduce mitochondrial activity, compromise membrane integrity, reduce cell viability and increase cytotoxicity. In turn, the lectins did not demonstrate any significant cytotoxicity to healthy cells. The long-term effect was that both lectins induced clonogenic death as a time-dependent effect. We used flow cytometry to confirm that the lectins tested interfered with the cell cycle of A549 cells, helped to stop the cycle in G1 and induced double labeling for annexin-V and 7-AAD. The morphological features, analyzed using optical and confocal microscopy, showed that there were alterations to the nucleus and cytoplasm, and apoptotic bodies were present. In addition, the lectins tested also showed an ability to interfere with the cell adhesion process and it was able to activate caspase 3/7 and 9. Finally, we also confirmed that amount of the pro-apoptotic protein Bax increased. Therefore, this study provides strong evidence that BTL and BSL have an antitumor effect on lung carcinoma cells, by inducing cell death by apoptosis, and activating the intrinsic pathway.